School Well-Being Reviewed from Interpersonal Relationships in Students - Apriliyani Kusuma Wardani; Sneha Sneha; Jewil Taslim; Beby Astri Tarigan; Winida Marpaung; Nur Afni Safarina (Mahesa Research Center, 2025)
This research was carried out at Raksana Private Junior High School in Medan. The study was conducted to determine the interpersonal relationship with school well-being among Raksana Medan Private Junior High School students. The population and sample determined in this study are 119 students of SMP Raksana Medan. Samples were obtained using the Disproportionate Stratified Random Sampling technique. Data was collected through questionnaire distribution efforts across samples. Furthermore, it is analyzed through the use of multiple regression analysis. The hypothesis test proves a correlation between School Well-Being and Interpersonal Relationships, as evidenced by the F test obtained F = 24.840 and p= 0.000(p<0.05). The Asusmsi test includes the normality test and the linearity test. Data analysis was done using multiple linear regression analysis techniques, assisted by SPSS Statistics 27 software for Windows. The resulting research showed a fundamental contribution of 18.3 percent of School Well-Being and interpersonal relationships; the remaining 81.7 percent came from other factors that were not studied. The results of this finding mean that higher school well-being can also increase students' interpersonal relationships. Conversely, low school well-being can also cause students' interpersonal relationships to be low.